Basic parameters of three star clusters in the Small Magellanic Cloud: Kron 11, Kron 63 and NGC 121 - Baume, Gustavo Luis (2008)
We present observations for three star clusters, Kron 11, Kron 63 and NGC 121, in the Small Magellanic Cloud. We have studied their structure and derived their fundamental parameters by means of their luminosity functions, their colour magnitude diagrams and the Padova suite of isochrones. NGC 121 is a well-studied object, for which we confirm previous evidence about its old age and low-metal content, and have found that it is an undergoing mass segregation. Kron 11 and Kron 63 are poorly populated clusters which had never been studied so far. Kron 11 is several gigayears younger than NGC 121, while Kron 63 is basically a very young star aggregate. Both clusters are immersed in dense stellar fields which share the same population properties, suggesting that in their cases, cluster ages are consistent with typical ages of field stars.